( p − 4 ) ( p + 1 ) ( p + 3 ) = ( n − 4 ) ( n + 4 )
Find the sum of all primes p satisfying the equation above, with n is a positive integer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If exist a case named: p ∣ 3 ( n + 2 ) ( n − 2 ) and 3 ∣ ( p 2 − 1 3 ) For some n that 3 ∣ ( n − 2 ) How about discuss for this? and more for replace 3 for another number?
Great estimates for Δ - nearly resorted to looking up closed forms for polynomials of forth order,,,
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: General Diophantine Equations - Problem Solving
Multiply the factors:
p 3 − 1 3 p + 4 = n 2 ⇒ p ( p 2 − 1 3 ) = ( n − 2 ) ( n + 2 ) .
Distinguish two cases
Case 1: p ∣ ( n − 2 ) and ( n + 2 ) ∣ ( p 2 − 1 3 )
that is
n = k p + 2 and p 2 = n k + 2 k + 1 3 ,
replacing the first in the second,
p 2 = k 2 p + 4 k + 1 3 ⇒ p 2 − k 2 p − 4 k − 1 3 = 0
which must provide entire solutions , therefore,
p = 2 k 2 ± Δ
in which Δ = k 4 + 1 6 k + 5 2 = m 2 with m ∈ Z .
With k = 1 there are no integer solutions ; in addition with k > 0
k 4 < Δ < ( k 2 + 8 ) 2
so Δ = ( k 2 + 2 i ) 2 with i = 1 , 2 , 3 .
Comparing the expressions as we get acceptable solutions
Δ = k 4 + 1 6 k + 5 2 = ( k 2 + 2 i ) 2 ⇒ k = 6 if i = 1 and k = 2 if i = 3 .
Substituting , we find that p = 3 7 , 7 .
Case 2: p ∣ ( n + 2 ) and ( n − 2 ) ∣ ( p 2 − 1 3 )
that is
n = k p − 2 and p 2 = n k − 2 k + 1 3 ,
replacing the first in the second it has
p 2 = k 2 p − 4 k + 1 3 ⇒ p 2 − k 2 p + 4 k − 1 3 = 0
which must provide entire solutions , therefore,
p = 2 k 2 ± Δ
in which Δ = k 4 − 1 6 k + 5 2 = m 2 with m ∈ Z .
With k = 1 there are no integer solutions; in addition with k > 1
( k 2 − 4 ) 2 < Δ ≤ ( k 2 + 2 ) 2
so Δ = ( k 2 − 2 i ) 2 with i = 1 , 0 , − 1 .
Comparing the expressions as we get acceptable solutions
Δ = k 4 − 1 6 k + 5 2 = ( k 2 − 2 i ) 2 ⇒ k = 2 if i = − 1 .
Substituting , we find that p = 5 .
Finally it follows that for n ≥ 0 p = 5 , 7 , 3 7 so 5 + 7 + 3 7 = 4 9 .